2007
DOI: 10.1148/radiol.2431060696
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry and Adequacy of CT-based Attenuation Correction for Pediatric PET: Phantom Study

Abstract: For pediatric patients, adequate attenuation correction can be obtained with very-low-dose CT (80 kVp, 5 mAs, 1.5:1 pitch), and such correction leads to a 100-fold dose reduction relative to diagnostic CT. For adults undergoing CT with 5 mAs and 1.5:1 pitch, the tube voltage needs to be increased to 120 kVp to prevent undercorrection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 15 publications
2
58
0
1
Order By: Relevance
“…If anatomic correlation of the PET image is not necessary, lower tube voltages and currents can be used without degradation of the attenuation-corrected PET images (13). For a discussion of the tradeoffs and motivations for different CT acquisitions in pediatric PET/CT, readers are referred to the work by Gelfand and Lemen (14).…”
Section: Pet/ct Protocol Designmentioning
confidence: 99%
“…If anatomic correlation of the PET image is not necessary, lower tube voltages and currents can be used without degradation of the attenuation-corrected PET images (13). For a discussion of the tradeoffs and motivations for different CT acquisitions in pediatric PET/CT, readers are referred to the work by Gelfand and Lemen (14).…”
Section: Pet/ct Protocol Designmentioning
confidence: 99%
“…The survey results reported here indicated that there is considerable variation in the acquisition of the CT component even among dedicated pediatric institutions, which further shows the potential need for standardization. Over the past decade, several groups have reported on the optimization of pediatric PET/CT (25,(41)(42)(43)(44). We have presented the Boston Children's approach as an option that uses AEC to manage radiation dose without setting specific levels for different-sized patients.…”
Section: Discussionmentioning
confidence: 99%
“…In PET/CT, the CT can be used for any of 3 distinct purposesattenuation correction, anatomic colocalization, or Dx interpretationor for a combination of these (21,25). Attenuation correction accounts for differences in the location of positron annihilation events and the degree to which tissues "attenuate" the PET annihilation photons.…”
Section: Acquisition Of Pet/ctmentioning
confidence: 99%
See 1 more Smart Citation
“…Fahey et al [15] evaluated dosimetry and the combination of both lower CT tube voltage and tube current for adequate CT-based attenuation correction for PET in pediatric patients, and CT acquisition parameters were shown to be adequate for pediatric but not for adult patients. Thus, although the use of a cylindrical phantom (200 mm in diameter and length) and a torso phantom (anteroposterior thickness of 280 mm and lateral thickness of 380 mm) allow to evaluation in patient of normal weight, these results may not be comparable to reported adequate CT tube current in obese patient.…”
Section: Discussionmentioning
confidence: 99%